Spatial Effects of Different Zebra Mussel Farming Strategies in an Eutrophic Baltic Lagoon - Friedland, René; Buer, Anna-Lucia; Dahlke, Sven; Schernewski, Gerald (Frontiers in Environmental Science, 2019)
Finding suitable places to establish a mussel farm is challenging, as many aspects like mussel growth, clearance effect and the risk of low oxygen conditions, have to be considered. We present a tailor-made approach, combining field experiments with a spatially explicit model tool, to support the planning process. A case study was set up in the German part of Szczecin (Oder) Lagoon (Baltic Sea), as it shows all typical eutrophication problems and has a strong need and high potential for nutrient retention measures. Farming zebra mussels (Dreissena polymorpha) is an innovative approach that utilizes a species which is often perceived as a pest. The practical applicability and water quality improvement potential was proven by a pilot farm. Combining the gained knowledge with the simulation model led to a cascade of mussel farm options that differ in purpose, location and biomass. Placing a mussel farm in an enclosed bay resulted in a remarkable water quality improvement (Secchi Depth increased up to 2 m), but the effect stayed local, the growth was limited and the potential annual nutrient removal reached a threshold of approximately 30 t N and 2.8 t P. The same nutrient removal could be reached with much smaller farms in an open sea area, whereas the change of water transparency or bottom oxygen conditions were neglectable. A maximal nutrient removal potential of 1,750 t N and 160 t P per year was estimated, when nearly the entire German part of Szczecin Lagoon with mussel farms was used. This led to a strong reduction of phytoplankton and an increase of Secchi Depth, but also a rising risk of anoxia. Overall, all mussel farm options are only a supportive measure, but not sufficient to reach the Good Environmental Status demanded by the Water Framework Directive. At once, the nutrient export from Szczecin Lagoon to the open Baltic was reduced by up to 3,500 t N and 420 t P per year, making the large-scale mussel farm option also a potential measure within the Marine Strategy Framework Directive.